2021
DOI: 10.14569/ijacsa.2021.0121231
|View full text |Cite
|
Sign up to set email alerts
|

English Semantic Similarity based on Map Reduce Classification for Agricultural Complaints

Abstract: Due to environmental changes, including global warming, climatic changes, ecological impact, and dangerous diseases like the Coronavirus epidemic. Since coronavirus is a hazardous disease that causes many deaths, government of Egypt undertook many strict regulations, including lockdowns and social distancing measures. These circumstances have affected agricultural experts' presence to help farmers or advise on solving agricultural problems. For helping this issue, this work focused on improving support for far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…This second output (output 2) of the proposed model will also provide the value of TF-IDF, which represents the weight of a text "i" in a tweet "j". As indicated in [28] TF-IDF provides the best performance of Fscore approximately 77.8%~94.8%, compared to other approaches, so its use guarantees the functionality of your application in determining the most relevant aspects of the satisfaction.…”
Section: Conditioning Sentiment Polarization Analysis and Data Extrac...mentioning
confidence: 98%
See 2 more Smart Citations
“…This second output (output 2) of the proposed model will also provide the value of TF-IDF, which represents the weight of a text "i" in a tweet "j". As indicated in [28] TF-IDF provides the best performance of Fscore approximately 77.8%~94.8%, compared to other approaches, so its use guarantees the functionality of your application in determining the most relevant aspects of the satisfaction.…”
Section: Conditioning Sentiment Polarization Analysis and Data Extrac...mentioning
confidence: 98%
“…Similarly, in [14] it is indicated that there is a significant improvement in Fscore when the data set is used after removing stopwords, so it is shown that the impact of removing stopwords is greater in TF-IDF than in TF-IDF that of fasttext. Likewise, in [28] it is pointed out that TF-IDF provides the best performance in determining the most relevant aspects of satisfaction. This was reflected in its results, where the system made an F score with 0.939 using TF-IDF, then around 0.899 in the TF, due to this, it is indicated that the system will be fast and reliable.…”
Section: Conditioning Sentiment Polarization Analysis and Data Extrac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Word vectors are created after preprocessing and classifying the farmer text and agriculture dataset. Then, we apply LSA [29], [30] to calculate the semantic similarity between the farmer text and the available agriculture dataset. LSA is a powerful corpus-based technique for calculating semantic similarity.…”
Section: Applying Lsamentioning
confidence: 99%
“…There are two measures of knowledge-based similarity that are semantic similarity and semantic relatedness. While in corpus-based similarity, it is a semantic similarity metric that determines how similar two terms are which is based on the large corpora's information such as HAL, LSA, ESA, and NGD [2,4,5]. In this research, the corpus-based similarity is the focus research similarity metric, especially the use of Latent Semantic analysis LSA.…”
Section: Introductionmentioning
confidence: 99%